Mitigation Of Non-Natural Disaster Outbreaks Through Increasing Awareness Of The COVID-19 Protocol In Mayang Village, Jember Indonesia: Mitigasi Bencana Non-Alam Wabah Penyakit Melalui Peningkatan Kesadaran Protokol Covid-19 Pada Masyarakat Desa Mayang Jember - Sutawardana, Jon Hafan; Hakam, Mulia; Nistiandani, Ana; Siswoyo, Siswoyo (DEDIKASI SAINTEK Jurnal Pengabdian Masyarakat, 2022)
At the end of the COVID-19 Pandemic, as it is today, people tend to lose their self-awareness regarding implementing their health protocols. On the other hand, a new variant of Covid 19 threatens public health, as evidenced by the recent increase in the number of cases in Indonesia. The community needs to get educated about mitigating non-natural disasters of the Covid 19 outbreak, so they can prepare themselves when the danger of this outbreak re-emerges in the community through self-awareness of the Covid 19 Protocol. The time of health education is about 60 minutes. Health education methods are used through lectures, discussions, and demonstrations using information media such as LCD projectors, leaflets, posters, and X-banners. Understanding evaluation methods using pre-test and post-test. The community showed enthusiasm during the activity, as evidenced by the many questions asked. Participants could also practice washing their hands properly and wearing a mask. When the verbal evaluation was carried out, participants could also answer the questions the teaching team posed correctly. The results of the written test evaluation showed an increase in the average value, namely from the pre-test score of 70.5 to 90.1 for the post-test average value. The community expressed their commitment to implementing the COVID-19 protocol in their daily lives to prevent the spread of COVID-19 cases.